THE INTERNET: INSTRUMENT OF SOCIALIZATION AND PROMOTION OF THE DECISIONAL AUTONOMY - Sobrado de Freitas, Riva; Zilio, Daniela (Unoesc International Legal Seminar, 2017)
This article aims to inquire if the internet can serve as mean of socialization, through the promotion of the individuals’ decisional autonomy, despite much talking about its influence in the social isolation. It has as problem the questioning about if the internet can serve as instrument of socialization and as a way of promoting the decisional autonomy of individuals, its users. To reach the purpose, it was done a bibliographical exploratory-explanatory search, qualitative, using the deductive method. As a search result, in summary, it has that, therefore in certain and specific situations, surely, the internet can favor the social isolation, since used according with the dictates recommended by common sense, with parsimony and respecting the limits of legality, can favor the socialization of individuals, and promote the improvement of their decisional autonomy. Concluding, therefore, that, the positive consequences related to the use of internet are really important, even in relation to the aspect of sociability and autonomous development. Keywords: Internet; Decisional Autonomy; Socialization; Social Isolation.